Mucosa-associated lymphoid tissue lymphoma in labial minor salivary glands - case report and literature review - Oba, Marina Kimie; de-Macedo, Leandro Dorigan; Motta, Ana Carolina Fragoso; Ricz, Hilton Marcos Alves; de-Freitas, Luiz Carlos Conti; Saggioro, Fabiano Pinto; Innocentini, Lara Maria Alencar Ramos (Journal of Oral Diagnosis, 2019)
Mucosa-associated lymphatic tissue (MALT) lymphomas commonly occur in the stomach however, rare cases of MALT lymphomas involve the minor salivary gland. We did a literature review and described the fourth case in the English literature of adults affected by a MALT lymphoma in the lip. A 68-year-old woman with probable primary Sjögren’s syndrome (SS) was referred to our dentistry and stomatology service, complaining that her lower lip had progressively thickened during the past 4 years. An incisional biopsy was performed, and the microscopic examination showed a dense, diffuse lymphoplasmacytic infiltration of the salivary glands, with plasmacytic differentiation. The immunohisto- chemical analysis revealed diffuse positivity of the neoplastic cells for CD20 and BCL-2; the plasma cells were positive for CD138 and Lambda, which was consistent with MALT lymphoma. SS and Immunoglobulin G4-related disease were excluded. The total regression of the lesion was obtained after treatment with surgery, chemotherapy, and radiotherapy.